Atlantis and caryatids: the humanities in the dungeon of a modern university - Rossman, Vadym (Actual Problems of Mind, 2021)
The essay provides an overview of the current position of humanities within contemporary universities with special emphasis on the universities in the United States. The current trend is to suppress humanities in order to better prepare students for their practical careers. In this context humanities are often seen as a burden and a liability rather than an asset. As a result, the courses in classical humanities disciplines are eliminated or downplayed in favor of courses in technology, business, computer science and other STEM disciplines. This attitude has serious consequences for the structure of contemporary university, where effective managers replace not very effective professors. It is no wonder that humanities occupy the lowest levels in the hierarchy of needs of contemporary consumer society. While it appears that liberal arts professors should feel at home at the university, in reality they are treated there as guest workers. Paradoxically, the neoliberal evaluation system of the performance of the humanities professors acquired many features of the old industrial production system emphasizing quantitative metrics such as number of publications. Ironically, these outdated antiquarian criteria were abandoned long time ago even in the corporate and industrial setting. Fetishization of technical innovations is an aspect of the ultimately irrational neoliberal system where policy innovations are persistently underestimated and discounted . However, many economic problems have their roots in the negligence of humanitarian issues. In such a system where «ideal goods» are completely neglected humans serve the economy, not the economy serves the humanity. The neoliberal ideologists that dominate in contemporary university administrations project the relationships between things upon the relations between human beings. This attitude deprives contemporary universities of their historical functions and responsibilities and transform them into trade school.